Small holes, big impact: Stomata in plant–pathogen–climate epic trifecta - Hou, Shuguo; Rodrigues, Olivier; Liu, Zunyong; Shan, Libo; He, Ping (Molecular plant, 2024)
The regulation of stomatal aperture opening and closure represents an evolutionary battle between plants and pathogens, characterized by adaptive strategies that influence both plant resistance and pathogen virulence. The ongoing climate change introduces further complexity, affecting pathogen invasion and host immunity. This review delves into recent advances on our understanding of the mechanisms governing immunity-related stomatal movement and patterning with an emphasis on the regulation of stomatal opening and closure dynamics by pathogen patterns and host phytocytokines. In addition, the review explores how climate changes impact plant–pathogen interactions by modulating stomatal behavior. In light of the pressing challenges associated with food security and the unpredictable nature of climate changes, future research in this field, which includes the investigation of spatiotemporal regulation and engineering of stomatal immunity, emerges as a promising avenue for enhancing crop resilience and contributing to climate control strategies. Precise regulation of stomatal movement ensures plant resilience against pathogen infections and ever-fluctuating dynamics of the environment. This review navigates recent progress in revealing the intricate signaling mechanisms governing stomatal movement dynamics and patterning in plants upon pathogen infections under the shifting climate paradigms.